Plasma-derived exosomes contribute to inflammation via the TLR9-NF-κB pathway in chronic heart failure patients. (July 2017) - Ye, Wei; Tang, Xiaojun; Yang, Zhengquan; Liu, Chu; Zhang, Xin; Jin, Jing; Lyu, Jianxin
Highlights: Plasma-derived exosomes carried mtDNA. Exosomes contribute to inflammation through the mtDNA-TLR9-NF-κB pathway. Chloroquine can block this pathway. Abstract: Exosomes are small vesicles that contain proteins, DNA and RNA, and play an important role in inflammation; however, the underlying mechanism remains unclear. In the present study, we found increased plasma-derived exosomes in chronic heart failure patients compared with healthy controls. Further, our data demonstrated that plasma-derived exosomes carried mtDNA, and triggered an inflammatory response via the TLR9-NF-κB pathway, as well, the inflammatory effect was closely related to exosomal mtDNA copy number. However, the effect could be blocked by chloroquine (CQ), a TLR9 inhibitor. These findings reveal a new mechanism of exosome-induced inflammation, and provide a new perspective for intervention and treatment of inflammation-related diseases, such as chronic heart failure.